Analysis of Health Level Assessment of Sharia Saving-Loan and Financing Cooperative - Ibrahim, Muhammad Ridwan; Meini, Zumratul (Hasanuddin Economics and Business Review, 2022)
In running their business, cooperatives need to conduct performance evaluation to determine its health level and improve the quality in the following years. KSPPS BMT Huwaiza is one of the cooperatives that provides loan and financing with mudharabah, murabahah, and ijarah contracts. In the midst of this Covid-19 pandemic, BMT Huwaiza managed to get government trust to receive revolving fund in order to support its activities. Thus, it is important to analyze the health level of BMT Huwaiza considering that this cooperative is responsible for the sustainability of the revolving fund. The performance evaluation on KSPPS BMT Huwaiza in 2017 - 2019 resulted in a health level of "Fairly Healthy" in 2017 with the score of 67.30 and 2018 with 70.95, and "Healthy" in 2019 having score of 84.60. Nevertheless, it is necessary for BMT Huwaiza to carry out further evaluation, particularly in capital and earning asset quality aspect which is still not optimal based on the assessment of health level of this cooperative. For cooperative members, by knowing the condition of current health level of the cooperative, it is hoped that they will increasingly believe that the fund managed by BMT Huwaiza will be able to continue providing benefits in the years to come.